Effects of school-based physical activity programs on executive function development in children: a systematic review - González-del-Castillo, Javier; Barbero-Alcocer, Irene (Frontiers in Psychology, 2025)
BackgroundExecutive functions (EF) are core cognitive processes that support self-regulation, learning, and behavioral flexibility in childhood. Structured physical activity (PA) programs implemented in school settings have been proposed as a means to enhance EF, but previous findings are inconsistent due to variations in intervention design, cognitive demands, and measurement strategies. This review offers an updated synthesis by focusing exclusively on school-based interventions in primary school children and including studies with neurophysiological outcomes.MethodsA systematic search was conducted in PubMed, SCOPUS, Web of Science, and EBSCO for studies published between January 2015 and March 2025. Eligible studies were randomized or cluster-randomized trials evaluating structured PA programs targeting EF in children aged 6–12 years. Methodological quality was assessed using a custom checklist aligned with Cochrane ROB-2 criteria. Due to heterogeneity in intervention formats and outcome measures, a narrative synthesis was conducted.ResultsTen studies met the inclusion criteria (total N ≈ 2,400). Short, cognitively engaging exercise sessions, such as rhythm-based activities or task-switching drills, were frequently associated with immediate improvements in inhibitory control. Longer-term interventions delivered over several weeks showed more robust and consistent benefits, particularly for inhibitory control and working memory. Positive effects were reported in 6 of 8 studies assessing inhibition, 5 of 6 on working memory, and 3 of 4 on cognitive flexibility. Some studies using fNIRS and EEG reported changes in prefrontal activation, suggesting potential functional enhancement. However, overall methodological quality was moderate, with common limitations in blinding and protocol transparency.ConclusionSchool-based physical activity can support EF development in children, especially when interventions are sustained and cognitively demanding. Effects are strongest for inhibition and working memory, while gains in cognitive flexibility appear less consistent and may require greater novelty and task variability. Future trials should refine intervention parameters, apply standardized EF assessments, and explore individual variability to guide evidence-based educational applications.Systematic review registrationCRD420251084225, https://www.crd.york.ac.uk/PROSPERO/view/CRD420251084225.